Presentation and Management of Displaced Lateral Condylar Mass Fractures With Ipsilateral Displaced Olecranon Fractures in Two Pediatric Cases. (February 2020) - Look, Nicole; Erickson, Mark; Sibbel, Sarah E.
Abstract: Cases: Two pediatric patients, aged 4 and 6-years-old, presented to a level one children's hospital with displaced lateral condylar mass (LCM) and ipsilateral displaced olecranon fractures after falling directly on to the affected extremity. Both patients underwent surgical fixation of the fractures, one of whom was found to have a laterally dislocated radial head intra-operatively. While one of the patients underwent open reduction internal fixation (ORIF) of both the LCM and olecranon fractures, the other patient underwent ORIF of the LCM and closed reduction percutaneous pinning (CRPP) of the olecranon fracture. Conclusions: Both patients were treated immediately upon presentation. They went on to full recovery with well-healed fractures and return of function to the affected extremity. Appropriate surgical management with ORIF versus CRPP may depend on displacement of the fractures and/or involvement of the radial head. Due to the rarity of this fracture combination, it can be difficult to identify in the acute setting. Most complications arise when the LCM-olecranon fractures go untreated. Therefore, it is imperative to have a high suspicion for multiple injuries at the elbow when a pediatric patient presents with elbow pain and swelling after a fall.